Building experiential live campaigns for social media - Vuorenmaa, Emma (My University, 2018)
Despite the prominence of social media and the increasing interest towards experiential live marketing, no prior studies have evaluated how organizations can successfully create experiential live campaigns (ELCs) in social media. This study draws together the framework for building ELCs in offline environments and the framework for creating virtual experiences in online marketplaces. Annexing the two concepts enabled the author to develop a theoretical framework for investigating how virtual environments impact the design and implementation of, what can be called, virtual experiential live campaigns (vELCs). Study was conducted qualitatively by examining a case campaign ‘Checkout247’. Data for the analysis was gathered through interviews with creators of the campaign and netnographic analysis on 3000 consumer comments on organizators’ brand communities. Based on findings, author developed a modified framework for building vELCs to highlight the main differences between ELCs in offline and online environments. Results enabled the author to conclude that virtual experiential marketing can serve as an effective tool for designing and implementing ELCs in social media, and that social media indeed can serve as an impactful and cost-efficient channel for delivering virtual experiences.